A Novel NAC Transcription Factor, PbeNAC1, of Pyrus betulifolia Confers Cold and Drought Tolerance via Interacting with PbeDREBs and Activating the Expression of Stress-Responsive Genes - Jin, Cong; Li, Kong-Qing; Xu, Xiao-Yong; Zhang, Hu-Ping; Chen, Hui-Xian; Chen, Yu-Hong; Hao, Jing; Wang, Yang; Huang, Xiao-San; Zhang, Shao-Ling (Frontiers in Plant Science, 2017)
NAC (NAM, ATAF, and CUC) transcription factors are important regulator in abiotic stress and plant development. However, knowledge concerning the functions of plant NAC TFs functioning in stress tolerance and the underlying molecular basis are still limited. In this study, we report functional characterization of the NAC TF, PbeNAC1, isolated from Pyrus betulifolia. PbeNAC1 were greatly induced by cold and drought, while salt stress had little effect on expression. PbeNAC1 was localized in the nuclei showed transactivation activity. Overexpression of PbeNAC1 conferred enhanced tolerance to multiple stresses, including cold and drought, as supported by lower levels of reactive oxygen species, higher survival rate, higher activities of enzymes, relative to wild-type (WT). In addition, steady-state mRNA levels of fifteen stress-responsive genes coding for either functional or regulatory proteins were higher levels in the transgenic plants relative to the WT with drought or cold treatment. yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays showed that PbeNAC1 protein can physically interact with PbeDREB1 and PbeDREB2A. Taken together, these results demonstrate that pear PbeNAC1 plays an important role in improving stress tolerance, possibly by interacting with PbeDREB1 and PbeDREB2A to enhance the mRNA levels of some stress-associated genes.